2021
DOI: 10.3390/en14206809
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Incorporating Rail Transport into a Zero-Emission Urban Deliveries System: Application of Light Freight Railway (LFR) Electric Trains

Abstract: This paper addresses the issue of incorporating rail transport into an urban delivery system. Its main purpose was to identify the possibilities of utilising rail transport in a Zero-emission Urban Delivery System (ZUDS) by applying Light Freight Railway (LFR) electric trains. The study applied the following research methods: literature review, observation, case study, and mathematical computations. In order to estimate the volume of transport external costs reduction resulting from shifting urban deliveries f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 107 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…This, in turn, should be analyzed alongside technical efficiency in the context of specific cities and projects. Analyzed papers, focused on description of advantages and barriers related to freight tram implementation, did not present any specific method to implement the freight tram transport or only described existing attempts of freight deliveries by trams [22][23][24][25][26][31][32][33][34][35][36]. Only one paper by Behiri et al [28] presented the mathematical model but had different optimization criterion (the objective function expressed the minimization of the total waiting time of all demands in their departure stations).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This, in turn, should be analyzed alongside technical efficiency in the context of specific cities and projects. Analyzed papers, focused on description of advantages and barriers related to freight tram implementation, did not present any specific method to implement the freight tram transport or only described existing attempts of freight deliveries by trams [22][23][24][25][26][31][32][33][34][35][36]. Only one paper by Behiri et al [28] presented the mathematical model but had different optimization criterion (the objective function expressed the minimization of the total waiting time of all demands in their departure stations).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Behrends [31,32] showed that the environmental benefits of a modal shift from road to rail in urban areas depended on the location of the intermodal terminal and destination point, and identified possible actions at a local level to improve both competitiveness and environmental benefits. The environmental benefits of implementing a light freight railway system were calculated in research provided by Pietrzak et al [33]. In addition, De Langhe et al [22] stated that only viable projects from an economic and a socioeconomic perspective have a chance of success.…”
Section: Use Of Freight Tramsmentioning
confidence: 99%
“…The issue of energy consumption is multidimensional, including not only factors related to the level of traction fuel or traction energy consumption but also other factors. This includes, among others, such elements as the structure of rolling stock (wagons and traction) [2] or the type of traction vehicles and their drive [2,84,87] (e.g., electricincluding cells [88][89][90], hybrid [91], hydrogen [92,93] and others), as well as issues of railway infrastructure [87,94,95], rail traffic control systems [95][96][97], and even the organization of rail traffic and transport [90,[95][96][97], or the ability to properly conduct rolling stock (eco-driving [98]). The sources of energy consumption in rail transport are, on the one hand, technical, and on the other are organizational, social, environmental, and economic, which favor the adaptation of the system, management, and global development of transport [99].…”
Section: Minimizing the Energy Consumption Of Transport In The Contex...mentioning
confidence: 99%
“…Importantly, the application of EFVs may bring tangible benefits in terms of mitigating the TS's impacts on the natural environment and human life and health (reduced levels of emissions and noise); nonetheless, it does not eliminate all the nuisances caused by UFT. For example, it does not reduce congestion and does not improve pedestrians' and cyclists' safety [91].…”
mentioning
confidence: 99%